Investor Sentiment from Google Searches and Its Impact on the Stock Market - Gupta, Purnima; Gupta, Nikhil (Indian Journal of Research in Capital Markets, 2025)
Purpose : This study investigated the influence of investor sentiment—proxied through Google search trends—on stock market movements in India. With behavioral finance gaining prominence, the research aimed to quantify how digital search behavior reflected investor mood and impacted market dynamics. Methodology : Using weekly Google search data for finance-related keywords, the study constructed a sentiment index through the Affin lexicon. This index was analyzed alongside macroeconomic indicators and stock market variables using stepwise regression and lead–lag analysis. Structural breaks were identified to assess shifts in sentiment impact over time. Findings : The results revealed a significant relationship between investor sentiment and stock market performance. Specifically, heightened search activity correlated with increased market volatility and directional shifts. The sentiment index demonstrated predictive power, especially during periods of economic uncertainty and policy announcements. Practical Implications : The findings suggested that Google search trends could serve as a real-time proxy for investor mood, offering valuable insights for portfolio managers, analysts, and policymakers. Incorporating sentiment analytics into forecasting models might enhance market timing and risk assessment strategies. Originality/Value : Unlike traditional sentiment measures, this study leveraged publicly available digital search data to construct a dynamic sentiment index. It contributed to behavioral finance literature by integrating technology-driven sentiment tracking with empirical market analysis in the Indian context.